Motivational profiles of learners of multiple foreign languages: A self-determination theory perspective. (June 2022) - Liu, Meng; Oga-Baldwin, W.L.Quint
Abstract: Adopting a person-centred and multilingual perspective, this study drew on self-determination theory and used latent profile analysis to investigate the motivational profiles of learners of multiple foreign languages. Chinese tertiary-level students (N = 523), concurrently studying English and a language other than English (LOTE), participated in the research. Latent profile analysis identified four groups for English motivation (High Quantity, Moderate Quality, Poor Quality and Amotivated) and three groups for LOTEs motivation (High Quantity, Medial and Amotivated). Our findings revealed high between-person and between-language heterogeneity in profile distribution, profile combination, and profile association with emotions. Specifically, negative emotion was more predictive of English motivational quality whereas positive emotion was more predictive of LOTEs motivational quality. Our results also suggest that making LOTEs compulsory is not sufficient to motivate students, as evidenced by the Medial profile being the normative profile unique to LOTEs. Regarding profile combinations, the best performing profile (High Quantity) was also the most likely shared profile by the same individual. While most learners had different profiles for different languages, it was extremely unlikely for the same individual to have profiles of opposite configurations. Our findings demonstrate the utility of combining person-centred techniques with a multilingual perceptive to produce a more nuanced and precise understanding of language learning motivation.